Food Allergens and Methods for Producing Hypoallergenic Foods - Danil A. Gromov; Anna V. Borisova; Vladimir V. Bakharev (Техника и технология пищевых производств)
Introduction. Healthy nutrition is one of the global problems that humanity is facing today, of which food safety and food allergies are the most relevant issues. A lot of chemicals used as food raw materials possess allergenic properties. Food producers are only beginning to realize the scale of this problem. As a result, hypoallergenic products and methods of food allergy prevention are at an early stage of development. Study objects and methods. The paper is a review of twenty years of research on food allergy. Results and discussion. The article describes the main sources of food allergens and allergenic proteins of plant and animal origin. It also gives various classifications of food allergens in terms of their stability and ability to maintain antigenic properties after processing, as well as provides methods for allergenicity reduction and hypoallergenic food production. Conclusion. Thermal and enzymatic processing are currently the most popular methods of reducing allergenicity of food raw materials. New approaches are based on enzymatic activity of microorganisms, the chemical modification of allergenic proteins, and the removal of allergenic proteins by binding them into complexes. The combination of enzymatic processing with high hydrostatic pressure or high-intensity ultrasound is the most promising direction in the production of hypoallergenic raw materials. Other promising methods are based on the enzymatic activity of microorganisms, chemical modification of allergenic proteins, and complexation with polyphenols, anthocyanins, etc. The future lies with genetic modification, which, however, still remains too complex, time-consuming, and understudied. Most novel methods need clinical trials to confirm the possibility of their use for commercial hypoallergenic food production.